Experimental Investigation Of MQL Turning Parameters On Surface Quality And Tool Wear Toward Green Machining Practices - E'ep Fadil Abdilah Gobel; Muhammad Rismanto; Kristian Selleng; Awal Syahrani Sirajuddin; Iskandar Iskandar; Anjar Asmara (Politeknik Negeri Lhokseumawe, 2026)
This study aims to determine the effect of spindle speed and air pressure on surface roughness and tool wear in the turning process of S45C steel using the Minimum Quantity Lubrication (MQL) system with used cooking oil as an environmentally friendly alternative cutting fluid. The spindle speed was varied at 800, 1000, and 1200 rpm, while the air pressure was set at 1, 2, and 3 bar. The experiments were carried out on a conventional lathe machine with controlled variables including the S45C workpiece material, a feed rate of 0.017 mm/rev, a depth of cut of 0.5 mm, and the use of a carbide insert tool. The dependent variables observed were surface roughness and tool wear. The results show that the application of the MQL system significantly reduced surface roughness and slowed down tool wear compared to dry cutting. The lowest surface roughness value was obtained at a spindle speed of 800 rpm and an air pressure of 2 bar under MQL conditions, while the highest tool wear occurred at 800 rpm and 1 bar without MQL. An air pressure of 2 bar provided the best balance between lubrication and cooling effects, maintaining the stability of the lubricant in the cutting zone. The combination of MQL at 2 bar air pressure and 800 rpm spindle speed proved effective in producing a smoother surface finish, extending tool life, and supporting green manufacturing practices through the utilization of used cooking oil as an eco-friendly alternative cutting fluid.